A Simplified PWM Technique for Isolated DC-DC Converter Fed Switched Capacitor Multi-Level Inverter for Distributed Generation - Mmanjunath BM; Ashok Kumar D V; Vijaya Kumar M (Institute of Advanced Engineering and Science, 2017)
This paper presents a novel simplied PWM technique to drive switched capacitor type multi-level inverter fed from isolated type DC-DC converter for distributed generation. Distributed generation (DG) is renowned power generation at point of utility with no environmental aects and reduces transmission line losses. Photo-voltaic system is considered as renewable energy source for DG and the low voltage from PV system is boosted to required voltage using an isolated type single-input multi-output (SIMO) DC-DC converter. DC output from isolated SIMO DC-DC converter is fed to switched capacitor type multi-level inverter (SC-MLI) to feed the AC load. Isolated SIMO DC-DC converter apart from boosting the DG output voltage, also eliminates the problem of voltage unbalancing in SC-MLI topology. Closed loop operation of SIMO DC-DC converter employs only single PI controller instead of three controllers was presented in this paper. Modes of operation of SC-MLI and Novel PWM switching pattern was explained. Simulation of proposed system was developed using MATLAB/SIMULINK software. The prototype was developed for the proposed system and hardware results are also shown.